(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The geriatric population frequently has femur inter-trochanteric fractures. The key factors contributing to the increased occurrence of these fractures include urbanization and sedentary lifestyle. Due to osteoporosis, there is a lower prevalence of inter- trochanteric femur fractures in men than in women. The comparison of PFN (vs. DHS) treatment of intertrochanteric fractures is the objective. To assess the effectiveness of the DH (Dynamic Hip) Screw (VS) PF (Proximal Femoral) Nail for femur inter-trochanteric fracture, we conducted a narrative review. For the purpose of determining which implant is superior, a thorough electronic search of literature was conducted in PUB-MED, Google Scholar, and reference checking. Some studies demonstrate that PF Nail is superior to DH Screw, while other studies show the opposite. Both operations are tried-and-true, absolute, and call for a fair degree of skill. The operating surgeon’s preference for a particular approach will ultimately determine the choice.